2018
DOI: 10.1021/jacs.8b03828
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into Diblock Copolymer Nanoparticle–Crystal Interactions Revealed via in Situ Atomic Force Microscopy

Abstract: Recently, it has become clear that a range of nanoparticles can be occluded within single crystals to form nanocomposites. Calcite is a much-studied model, but even in this case we have yet to fully understand the details of the nanoscale interactions at the organic-inorganic interface that lead to occlusion. Here, a series of diblock copolymer nanoparticles with well-defined surface chemistries were visualized interacting with a growing calcite surface using in situ atomic force microscopy. These nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 52 publications
1
44
0
Order By: Relevance
“…Recently, Estroff and coworkers demonstrated three modes of interaction between the nanoparticles and the growing calcite surface via in situ AFM studies: (i) nanoparticle attachment followed by detachment, (ii) nanoparticle, and (iii) incorporation of the nanoparticle by the growing crystals. 62 Which Parameters Dictate Uniform Occlusion? Empirically, it has been shown that anionic surface character is important for driving nanoparticle occlusion within calcite.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Estroff and coworkers demonstrated three modes of interaction between the nanoparticles and the growing calcite surface via in situ AFM studies: (i) nanoparticle attachment followed by detachment, (ii) nanoparticle, and (iii) incorporation of the nanoparticle by the growing crystals. 62 Which Parameters Dictate Uniform Occlusion? Empirically, it has been shown that anionic surface character is important for driving nanoparticle occlusion within calcite.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] Not only do such synthetic routes provide a straightforward approach to the rational design of new hybrid materials with enhanced physical properties such as hardness, magnetism, color or strong fluorescence, [16][17][18][19][20] but they can also inform our understanding of biomineralization processes. [21][22][23][24] There is no doubt that the nanoparticle surface chemistry dictates their occlusion. [25][26][27] However, the precise design rules required for efficient nanoparticle occlusion within inorganic crystals have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, there is no specific requirement for the nanoparticle surface chemistry because the nanoparticles are merely physically entrapped within an appropriate gel network. However, for active nanoparticle occlusion within growing inorganic crystals, the nanoparticle surface chemistry dictates whether occlusion occurs and also to what extent . In the present study, nanoparticles with low phosphate content are preferentially occluded within the near‐surface of the calcite crystals (see Figure b and Figure S4), presumably because there are insufficient anionic groups to ensure adequate binding to the growing crystal surface.…”
Section: Methodsmentioning
confidence: 63%
“…Nanoparticle occlusion within inorganic crystals is a complex process that is influenced by many parameters . Liu and co‐workers reported that nanoparticles can be passively incorporated into calcite using a gel‐trapping method .…”
Section: Methodsmentioning
confidence: 99%